Analisis Keselamatan Pelayaran Berbasis Analytical Hierarchy Process PT. ASDP Indonesia Ferry (Persero) Bakauheni Lampung Selatan - Hijrah Faqih Ramadhan; Purwanto Purwanto; Sunu Arsy Pratomo (Globe: Publikasi Ilmu Teknik, Teknologi Kebumian, Ilmu Perkapalan, 2024)
The transportation sector has a very vital and strategic contribution to national development, because of its role as a driver and driver of development activities and a glue for the gap between regions. Ferry transportation is transportation that functions as a bridge connecting one area with another area separated by waters. The purpose of writing this paper This article was written to find out and explain the safety equipment standards, what types of safety equipment are there, and how many are there and how many crew members are on the ferry in accordance with applicable regulations. As well as the condition of passenger safety equipment on KMP. Sebuku, KMP. Portlink V, KMP. Jatra III and find out which ship is the most complete, and has the most safety equipment and crew on board. The method used in writing this paper uses the observation method, interviews, and literature studies. In this case, data collection is in the form of observation data, as well as a collection of documentation and data related to safety equipment.